Identification and Characterization of the Phosphate-Solubilizing Bacterium Pantoea sp. S32 in Reclamation Soil in Shanxi, China - Chen, Qian; Liu, Shanjiang (Frontiers in Microbiology, 2019)
Phosphate solubilizing bacteria (PSB) can convert insoluble forms of phosphorus (P) to accessible forms. Five highly efficient PSB strains, H22, Y11, Y14, Y34, and S32, were screened and isolated from an alfalfa rhizosphere in heavy metal-contaminated reclamation area in Shanxi Province, China. Based on morphological observations, 16S rRNA sequencing, cellular fatty acid composition analysis, and the BIOLOG test, H22, Y11, and Y34 were identified as Pseudomonas sp., while Y14 and S32 were identified as Pantoea sp. Among them, S32 showed the highest P-solubilizing efficiency in culture medium containing Ca3(PO4)2, lecithin, and powered phosphate rock. The culture medium conditions to obtain the highest P-solubilization efficiency were optimized as follows: the culture temperature was 30°C; the incubation time was 5 d; the initial pH was 7.0; and glucose served as the carbon source. Furthermore, the P-solubilization efficiency of S32 in media containing CaHPO4, lecithin, phosphate rock (PR), FePO4, or AlPO4 was determined to be 18.38%, 3.07%, 0.16%, 0.51%, or 2.62%, respectively. In addition, the acid and alkali phosphatase activities of S32 were tested as 6.94 U/100 mL and 4.12 U/100 mL, respectively. The soil inoculation experiment indicated that inoculation with S32 resulted in an obvious improvement in the available P of both the experimental and reclaimed soil. The rice seedling growth experiment also suggested that the application of S32 significantly increased the plant height, biomass, root growth, and P uptake of rice in both experimental and reclaimed soil. Taken together, the isolated S32 strain showed high P-solubilization capacity for both Pi and Po, and its ameliorative effect on reclaimed soil recovery provides the theoretical basis for crop development in the reclaimed soil of mine field.